Knowledge about hormone replacement therapy and its use among fifty years old women living in Gdynia and Sopot. Estimates from SOPKARD and GDYNIAKARD study - Mogilnaya, Irina; Rachoń, Dominik; Zdrojewski, Tomasz; Suchecka-Rachoń, Krystyna (Menopause Review/Przegląd Menopauzalny, 2005)
The aim of this study was to evaluate the knowledge and the prevalence of hormone replacement therapy (HRT) use among 50 year old inhabitants of the two cities in the north part of Poland: Gdynia and Sopot. Materials: The survey was conducted on a sample of 586 women (269 were postmenopausal and 317 were premenopausal) in the years 2002–2003. Results: Depending on the education level 56.4 to 93.5% of women have heard about HRT. Most of the women pointed out the improvement of well being as an advantage of HRT use. One out of five women knew that the use of HRT prevents osteoporosis development. Among the risks of HRT use, cancer was pointed out in the first place. During the study 29% of women were current users of HRT. The most often reason of not using HRT was the lack of information about such a therapeutic option. 20% of the women have never heard of HRT and 32% have never spoke with their doctors about the possibility of introducing such a treatment. One out of five women, which has heard about HRT, did not use it because according to them it was ”against the nature”. Only 12.5% from the women who have heard about it didn’t use it because they were afraid of cancer. 50% of women taking HRT were using transdermal continuous oestrogen therapy. Conclusions: The prevalence of HRT use among the 50 year old inhabitants of Gdynia and Sopot is two times higher compared to the whole Polish population (29% vs. 15.7%) and it is comparable to other European countries. The most often reason of not using HRT is the lack of information of such a therapeutic option.